Chemical Constituents of Cordia dichotoma G. Forst. - Consolacion Y. Ragasa & , Virgilio Ebajo Jr., Mariquit M. De Los Reyes & , Emelina H. Mandia, Maria Carmen S. Tan, Robert BrkljaÄa, Sylvia Urban (Journal of Applied Pharmaceutical Science, 2015)
Chemical investigation of the dichloromethane extracts of Cordia dichotoma G. Forst led to the isolation of β-sitosteryl-3β-glucopyranoside-6'-O-palmitate (1), nervonyl 4-hydroxy-trans-cinnamate ester (2), β-sitosterol (3), and chlorophyll a (4) from the leaves; and 4 and 1,2-dilinoleoyl-3-linolenoylglycerol (5) from the twigs. The structures of 1-5 were identified by comparison of their NMR data with those reported in the literature. The fatty acids in 1, 2 and 5 were deduced from ESI-MS data.
Keywords: Cordia dichotoma G. Forst, Boraginaceae, &beta; -sitosteryl-3&beta; -glucopyranoside-6' -O-palmitate, nervonyl 4-hydroxy-trans-cinnamate ester, &beta; -sitosterol, chlorophyll a, 1,2-dilinoleoyl-3-linolenoylglycerol.